2018
DOI: 10.1002/ange.201805042
|View full text |Cite
|
Sign up to set email alerts
|

Ultraparamagnetic Cells Formed through Intracellular Oxidation and Chelation of Paramagnetic Iron

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…While the current study demonstrated MR imaging of E. coli (F + ) and V. cholerae cells, DP1-phage may in principle be engineered to noninvasively monitor different bacterial targets by tuning one of the four phage coat proteins (keeping pVIII for DP1 fusion) to incorporate receptorbinding proteins from native phages with tropism towards the desired bacterial strain 30 . The present work also established preliminary proof-of-principle for in vivo imaging of bacteria pre-labeled with DP1phage, which may be useful for cell tracking applications involving the use of bacteria as live-cell therapeutics, especially if genetic modification of the bacterial strain to express reporter genes for noninvasive imaging [31][32][33] is not desirable or possible. In situ detection of pathogenic or commensal microorganisms in their animal host would however require DP1-phage to be delivered in vivo.…”
Section: Discussionmentioning
confidence: 80%
“…While the current study demonstrated MR imaging of E. coli (F + ) and V. cholerae cells, DP1-phage may in principle be engineered to noninvasively monitor different bacterial targets by tuning one of the four phage coat proteins (keeping pVIII for DP1 fusion) to incorporate receptorbinding proteins from native phages with tropism towards the desired bacterial strain 30 . The present work also established preliminary proof-of-principle for in vivo imaging of bacteria pre-labeled with DP1phage, which may be useful for cell tracking applications involving the use of bacteria as live-cell therapeutics, especially if genetic modification of the bacterial strain to express reporter genes for noninvasive imaging [31][32][33] is not desirable or possible. In situ detection of pathogenic or commensal microorganisms in their animal host would however require DP1-phage to be delivered in vivo.…”
Section: Discussionmentioning
confidence: 80%
“…While ferritin nanoparticles may be assembled inside cells with genetic encoding, the ensuing magnetization is much smaller than similarly-sized synthetic nanoparticles, which limits the sensitivity of the clustering mechanism for ferritin-based biosensing. [66] That said, the recent advent of several engineered iron-nucleating proteins with higher per-particle magnetic moments [39,[67][68][69][70] compared to ferritin provides a fresh set of biomolecular templates that could be used to sense dilute analytes based on nanoscale assembly and aggregation. The general feasibility of this approach has already been established by imaging streptavidin in yeast cells engineered to express a hypermagnetic variant of ferritin fused with streptavidin-binding peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in synthetic biology have enabled the enhancement of the capabilities of motile microorganisms without the usage of artificial components, such as programming genetically engineered bacteria to generate diverse, active components, including magnetic particles [128,129], gas-filled microstructures [130,131], therapeutic payloads [132], or responsive probes [133]. The synthetic biological approach, however, is beyond the scope of this work.…”
Section: Bio-hybrid Microswimmersmentioning
confidence: 99%